2022
DOI: 10.3390/pharmaceutics14040731
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Toxicity in Mice after High Activity Injections of 177Lu-PSMA-617

Abstract: Prostate cancer (PC) is one of the most common malignancies affecting men, with poor prognosis after progression to metastatic castration-resistant prostate cancer (mCRPC). Radioligand therapy (RLT) targeting the overexpressed PSMA on PC cells, with, e.g., 177Lu-PSMA-617, has been effective in reducing tumor burden and prolonging survival in mCRPC. However, it is not a curative method with kidney and bone marrow toxicity limiting the activity given to patients. Previous preclinical models have reported transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Other research groups did not observe severe hematotoxicity in immunocompetent mice after injection of up to sixfold higher activities of [ 177 Lu]Lu-PSMA-617 [ 30 , 35 ]. It has to be critically acknowledged that the application of such high activities would most probably not be possible without causing undesired hematological effects when using albumin-binding PSMA radioligands.…”
Section: Discussionmentioning
confidence: 99%
“…Other research groups did not observe severe hematotoxicity in immunocompetent mice after injection of up to sixfold higher activities of [ 177 Lu]Lu-PSMA-617 [ 30 , 35 ]. It has to be critically acknowledged that the application of such high activities would most probably not be possible without causing undesired hematological effects when using albumin-binding PSMA radioligands.…”
Section: Discussionmentioning
confidence: 99%
“…However, after 7 d, no significant difference was observed between the negative control and the treatment with lutetium radionanoparticles ( p > 0.05). Therefore, the observed toxicity can be attributed to a well-known and transient toxic effect of radiation on the bone marrow [ 38 , 40 ], but not to the nanoparticles themselves. That is, if the activation of DNA repair mechanisms was not sufficiently effective due to severe nanoparticle damage, the expected behavior would be, at least, like that of the positive control (colchicine), which did not occur.…”
Section: Resultsmentioning
confidence: 99%
“…The genotoxicity associated with the bone marrow irradiation was transient since a recovery in mice treated with [ 177 Lu]Lu−iFAP/iPSMA was observed after 7 d [ 38 , 40 ]. Therefore, genotoxicity was not observed as a consequence of an excess of free radicals induced from nanoparticles due to oxidative stress with a potential mutagenic effect [ 28 , 29 ], which confirmed that intravenous systemic administration is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Radiolabeling was performed similarly to previous work 27 . Freeze-dried PSMA-617 (MedChemExpress, Monmouth Junction, NJ, USA) was dissolved in chelexed 0.2 M ammonium acetate, pH 5.5, to a final concentration of 2 µg/µL.…”
Section: Methodsmentioning
confidence: 99%
“…In order to reach absorbed doses to the kidney that causes measurable damage, we have previously established that mice can recover from hematotoxicity caused by one injection of up to 200 MBq of [ 177 Lu]Lu-PSMA-617 27 . The aim of this study was to employ a high activity therapy delivered in three cycles of [ 177 Lu]Lu-PSMA-617 in a preclinical mouse model to achieve nephrotoxicity and analyze the effect of co-injecting rA1M on kidney function and blood cell counts.…”
Section: Introductionmentioning
confidence: 99%